Between threads and time: The re-creation of a 1925 bra (Revista de Ensino em Artes, Moda e Design, 2024)
This study aims to recreate a bra dated between 1925 and 1930, based on qualitative research utilizing bibliographic records (books, academic articles, theses, and dissertations), periodicals, catalogs from the era, and iconography, in addition to specialized literature on garment construction techniques (pattern making and sewing) for undergarments. However, its primary source was the study of an original garment from the collection of the Museu do Traje in Lisbon. The importance of studying original garments within collections is noteworthy, as it allows for the recreation not only of the aesthetic aspects, such as shape and design, but also the construction techniques of historical garments. This work distinguishes itself by also presenting the garment patterns and a step-by-step guide to their construction, thereby serving as a valuable resource for students, researchers, and other professionals in the field, particularly those involved in costume design for various types of performances.
Keywords: women’s clothing; clothing – history; clothing – pattern making